A novel intestinal rotation method for digestive reconstruction after combined pancreaticoduodenectomy and extended right hemicolectomy: A case report and surgical technique. (2017) - Takagi, Kosei; Yagi, Takahito; Umeda, Yuzo; Yoshida, Ryuichi; Nobuoka, Daisuke; Kuise, Takashi; Kumano, Kenjiro; Kojima, Takeshi; Fushimi, Takuro; Fujiwara, Toshiyoshi
Highlights: Pancreaticoduodenectomy (PD) along with extended right hemicolectomy (RH) is challenging. Practitioners must pay attention to twisting of the intestinal mesentery when reconstructing the digestive system. We developed an intestinal rotation method for digestive reconstruction. This method can be helpful for digestive reconstruction after combined PD and RH. Abstract: Introduction: Pancreaticoduodenectomy (PD) combined with extended right hemicolectomy (RH) is a challenging procedure for locally advanced malignancies. However, information concerning the reconstruction method of the digestive system is limited. Here, we present a case and surgical technique of a novel intestinal rotation method for digestive reconstruction after PD combined with RH. Presentation of case: A 62-year-old man with locally advanced pancreatic cancer received conversion surgery combined with PD and RH after preoperative chemotherapy. With respect to the reconstruction of the digestive system, the entire intestinal mesentery was rotated 180° forward counterclockwise around the axis of the superior mesenteric artery, and then the reconstruction, according to Child's method, was performed. The patient recovered without problems in gastroenterological functions after the operation. Discussion: With respect to the reconstruction of the digestive system in patients undergoing combined PD and RH, practitioners should pay close attention to twisting of the intestinal mesentery when bringing up the proximal jejunum for pancreatojejunostomy and hepatojejunostomy and the distal ileum for ileocolic anastomosis. This intestinal rotation method enables a smooth and uneventful reconstruction of the digestive system. Conclusion: This is the first detailed description of an intestinal rotation method for digestive reconstruction after combined PD and extended RH. The intestinal rotation method can be an alternative and helpful technical option for digestive reconstruction in patients with combined PD and RH.